The GA Among Giants. Gans’s Scene of Language and Culture Origin in Reference to Cassirer’s and Heidegger’s Visions of the Human - Złocka-Dąbrowska, Magdalena (Załącznik Kulturoznawczy, 2020)
This essay situates Eric Gans’s Generative Anthropology (GA) within Ernst Cassirer’s and Martin Heidegger’s intricate ontologies and validates GA as an applied ontology of language and culture. First, I will follow Gans’s suggestions for placing GA within a philosophical context, in particular, in terms of his situating of GA as a response to Heidegger’s Being and Time. I will then present Gans’s central concept of GA – the rise of language/ culture as the origin of the ‘human as human’ – a way of linking Gans’s system of representation with Cassirer’s system of symbolic forms. The description of the main components of Gans’s ‘scene’, namely: language, sign, community and violence, as responding to Cassirer’s and Heidegger’s respective understandings, will lead us to symbolic representation as opposed to a phenomenology that views forms merely as limitations for Being. I propose a mediating position between the competing claims of Cassirer and Heidegger, respectively, in Gans’s originary thinking, in the ‘explosion of language’ that allows the hermeneutics of the language of being (Dasein) to regain its presence.